عبدالله الطيب شاعر التراث: مكانته الأدبية وظواهر لغوية في ديوانه :بانات رامة = ʽAbdullah al-Ṭayyib a traditional poet: his literary standing and language features in his anthology: “Banāt Ramah” - Hussein, Nasr El Din Ibrahim Ahmed; Idris, Musa Said Taha (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يسعى الباحث من خلال اتباع المنهجين: الوصفي والتحليلي إلى دراسة موضوع عبدالله الطيب شاعر التراث: مكانته الأدبية وظواهر لغوية في ديوانه بانات راوة. حيث يبرز البحث مكانة عبدالله الطيب الأدبية، مبيناً اهتمامه بالتراث الشعري العربي والاقتداء به في أشعاره، كما يتناول الظواهر اللغوية التي تميّز بها هذا الديوان، ويهدف هذا البحث إلى إظهار مكانة عبدالله الطيب الأدبية واللغوية حيث يزخر شعره بكثير من الظواهر اللغوية الفنية التي أصبحت ظااهرة لغوية مميّزة لشعره. ************************************************************* This study, by making use of the descriptive and analytical methods, aims to explore the literary position of the ‘Abdullah al-Ṭayyib as a traditional poet and his language characteristics in his anthology “Banāt Ramah”. His literary position is pointed out through his interest in the Arabic poetic tradition and his commitment to it in his poems as well as the language characteristics which distinguish him in his anthology. The study concludes among others: that the poems of ‘Abdullah al-Ṭayyib are abundantly infused with aesthetical features of language, among them is the use of different symbols; some represent the nation while others represent the barren deserts. He made use of the style of the earlier Arabic traditional poets both in words and senses. His inclination to the traditional elements is rare in the time when contemporary poets mostly would turn away from it. Hence, he made use of some of the traditional openings and some phrases in the ancient traditional poems, thus earning himself a special characteristic as found in the anthology.